B-spline solution of singular boundary value problems - Çağlar, Nazan; Çağlar, Hikmet (ELSEVIER SCIENCE INC, 360 PARK AVE SOUTH, NEW YORK, NY 10010-1710 USA, 2006)
Homogeneous and non-homogenous singular boundary value problems (special case) are solved using B-splines. The original differential equation is modified at singular point then the boundary value problem is treated by using B-spline approximation. The method is tested on some model problems from the literature, and the numerical results are compared with exact solution. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: singular point; singular two-point boundary value problems; B-splines; numerical-solution; finite-difference; tekil nokta; tekil iki nokta sınır değer problemleri; sayısal çözüm; sonlu farklar